Comparative evaluation of postpartum IUCD versus interval IUCD at a tertiary care centre in Allahabad, India - Singh, Urvashi; Sonkar, Shubhangi; Yadav, Preeti; Dayal, Meena; Gupta, Veena; Saxena, Somya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The use of Cu T in postpartum period can provide long term and effective contraception and this study compares PPIUCD versus interval IUCD. Methods: 300 women enrolled in the study were divided into two groups. Postpartum group-150; Postplacental or within 10 minutes/intracaesarean/within 48 hrs of delivery. Interval Group 150; after 6 weeks of delivery / postmenstrual. Cu T 380A was used in the study. Contraindication for PPIUCD were between 48 hrs and 6 wks postpartum, chorioaminionitis, PROM >18 hrs, unresolved PPH and puerperal sepsis. All were followed up for 6 months. Results: The continuation rate at 6 months was 81.81% in interval group and 88.23% in postpartum group. Complications occurred in 15.33% cases after PPIUCD and in 19.33% cases after interval IUCD. Expulsion rate was significantly higher in PPIUCD as compared to interval insertions (6.96% v/s 2.2%; p value <0.05). Removal rate of IUCD was almost similar in both the groups (4% in PPIUCD v/s 6.0% in interval). Conclusions: PPIUCD is an effective, safe, convenient, low cost and long term method of postpartum contraception irrespective of the mode of delivery.